Effects of natural aging after pre-aging on clustering and bake-hardening behavior in an Al–Mg–Si alloy. (15th April 2016) - Aruga, Yasuhiro; Kozuka, Masaya; Takaki, Yasuo; Sato, Tatsuo
Abstract: Atom probe tomography (APT) analysis was used to characterize the clustered state after pre-aging at 90 °C (PA) and subsequent natural aging (NA) in an Al–0.62Mg–0.93Si (mass%) alloy. It was revealed that larger Si-rich clusters increase in number after prolonged NA. The long-term NA after PA is believed to promote the preferential aggregation of solute Si toward clusters formed during PA rather than the independent formation of Si-based clusters. The prolonged NA inhibits the hardness increase during bake-hardening (BH) treatment at 170 °C. The deterioration of the BH response appears to be due to the increase of the Si-rich clusters. Graphical abstract: